FORMULASI PENGHARMONISASIAN RANCANGAN PERATURAN PERUNDANG-UNDANGAN YANG DIBENTUK DI DAERAH - Ari Setyono (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
Ministerial Regulation is a regulation that is formed based on the authority and rules that are above it. The contents of ministerial regulations should be in line with all regulations, especially with regulations that have a higher position. Bearing in mind the higher legal principle of regulation can override the regulation under “Lex Superior Derogat Legi Inferior”. The fact is that there is a Ministerial Regulation whose material content is not in line with the above regulations, one of which is the Minister of Law and Human Rights Regulation. It is hoped that the objectives of this study are the Ministerial Regulations in line with higher-level regulations. This study uses a normative legal research method with an approach to the legislation. In this study secondary data is used as a source of research data. The results of this study confirm the legal enactment of the Minister of Law and Human Rights Regulation Number 22 of 2018 not by the legal principle because it is not in line with the above regulations namely Law Number 12 of 2011 concerning Formation of Laws and Law Number 23 of Year 2014 concerning Regional Government.